- #1

- 251

- 0

## Homework Statement

n+1 , n

[tex]\sum[/tex] (nCk-1) f(x)g(x) + [tex]\sum[/tex] (nCk) f(x)g(x)

k=1 , k = 0 (for first and second summations respectively)

I can't just say that that is equal to:

n+1

[tex]\sum[/tex] (n+1 C k) f(x)g(x)

k=0

since the (nC k-1) and (nC k) above are kind of illusionary, (n C k-1) starts at 1 and ends when k = n+1 so it's just exactly the same as the (nC k) summation

right?

thanks

## Homework Equations

n+1 C k = n C k-1 + n C k

## The Attempt at a Solution

see above